Hormonal responses to excessive training: influence of cross training - Flynn, M. G.; Pizza, F. X.; Brolinson, P. G. (International Journal of Sports Medicine, 1997)
The purpose of this investigation was to examine the changes in blood hormone levels elicited by increases in training volume. After 30 d of recording their training volume and intensity (normal training, 57.5 +/- 10.9 km.wk-1), 11 well-trained distance runners completed two randomly assigned 10 day periods of increased training volume (200% normal training). Each increased training regimen was preceded by two weeks of reduced training (80% normal training). The increased training regimens consisted of either running only (RT) at 200% of normal training distance or running (100% normal training) and cycling (kcal = 100% normal training: CT). During each increased training regimen the subjects ran 10 consecutive afternoons at a distance equivalent to 100% of normal training (approximately 75% VO2max) and performed eight additional morning sessions (0500-0800 h). During RT the subjects performed their morning workouts on a treadmill and during CT the workouts were performed on a bicycle ergometer. Blood samples were obtained (0500-0700 h) after 15 min supine rest after normal training, and before (day 0), on day five (day 5) and following ten days (day 11) of RT and CT. Serum was analyzed for testosterone, free testosterone, cortisol, adrenocorticotropic hormone, luteinizing hormone, and dehydroepiandrosterone sulfate. Free testosterone was significantly (p < 0.05) reduced on day 5 and day 11 of RT and CT compared to day 0 and total testosterone was lower on day 5 than day 0. However, no significant treatment or interaction effects were observed for total testosterone or free testosterone. Dehydroepiandrosterone sulfate was also significantly lower across time, i.e., day 11 was lower than day 0 and day 5; however, cortisol, adrenocorticotropic hormone, and luteinizing hormone were not significantly altered during RT or CT. The endocrine responses to an increased training volume with cross training and mode specific training were similar.